Humanitarian Framing of the 2025 Indonesian Demonstrations: A Comparative Analysis of NU Online and Suara Muhammadiyah - Sifa Aprilia Ersa; Fitri Yanti; Nadya Amalia Nasoetion (Universitas Ahmad Dahlan, 2026)
In the context of increasing public reliance on religious-based media as credible sources of information, Islamic media play an important role in shaping moral discourse and public interpretation of political events. The 2025 demonstrations in Indonesia raised various humanitarian concerns, including violence, student arrests, and human rights violations. This research aims to analyze how NU Online and Suara Muhammadiyah frame humanitarian issues in their coverage of the August–September 2025 demonstrations. The study employs a qualitative framing analysis using Robert Entman’s framing model. Data were collected from selected news articles published by both media outlets during the peak period of the demonstrations and analyzed comparatively to identify similarities and differences in framing patterns. The findings reveal that both media outlets emphasize humanitarian concerns but construct them through different interpretative frameworks influenced by their organizational orientations. NU Online tends to frame demonstrations through narratives of human rights, social justice, and protection of demonstrators, while Suara Muhammadiyah emphasizes social ethics, moderation, dialogue, and political stability. These differences indicate that Islamic online media function as active agents in constructing humanitarian discourse and shaping public understanding of political demonstrations. This study contributes theoretically to the development of framing theory in the context of Islamic digital media and enriches the literature on Islamic political communication. In practice, the findings suggest the importance of ethical, balanced framing in religious media coverage of political events discourse.